Analisis Kuantitatif Hasil Pertandingan Sepakbola Antara PS Barito Putera Melawan PSS Sleman Pada Leg Kedua Piala Indonesia 2019 - Yoangga Meinanto Meinanto; Achmad Widodo (Indonesian Journal of Kinanthropology (IJOK), 2022)
ABSTRACT Background: Football is a game that is very popular among various groups of children, teenagers, adults and parents throughout the world. In order to support a good football game, players are required to be able to do passing, dribbling, shooting, and ball possession. The purpose of this study is to quantitatively analyze the results of the football match between PS Barito Putera and PSS Sleman in the second leg of the 2019 Piala Indonesia. Methods: By using this type of research used is quantitative descriptive research known from match statistics data as skunder data Results: The research results show that the PS Barito Putera passing technique is superior by 81%, the dribbling technique PSS Sleman is superior with 65%, the shooting technique PSS Sleman is superior with 36% and the ball possession ps Barito Putera is superior with 60%. Conclusions: Other match data showed that the final score was obtained a draw of 3-3 and the shooting technique was the key to the team's failure in the match with data on the percentage of success of 69% (PS Barito Putera) and 64% (PSS Sleman). Keywords: Quantitative Analysis; Football Techniques; Piala Indonesia 2019